Impact of Forest Fire and Biotic Interference on the Bio-diversity of Eastern Ghats - Srivastava, Rajiv K.; Chidambaram, K.; Kumaravelu, G. (Indian Forester, 1999)
Impact of forest fire and biotic interference on bio-diversity of the Eastern Ghats due to human interference and man-animal conflict have been discussed.